Commande par Logique Floue d'un Filtre Actif Parallèle - SOUALMI, Djihane; DEBILOU, Mohammed said (université d'eloued, 2023)
"Electrical energy, mainly produced and distributed in the form of three-phase sinusoidal voltages, provides the electrical power necessary for the various loads on the electrical network. The latter records an increase in disturbances due to the increase in non-linear loads in number and type. Conventional solutions have been shown to be insufficient. By promoting some of the new fast components of energy electronics, modern and efficient solutions have emerged, and the work presented in this thesis addresses a solution modern for controlling harmonic pollution which is the filter parallel active. In this thesis, we present the study and simulation of the two-level parallel active compensator. The two parameters that require fine tuning for better compensation are the inverter supply voltage (active filter) and the harmonic current or voltage. After a reminder of the origins, and the effects of harmonic pollution on networks electrical, the various solutions for cleaning up the electrical network we study the structure of the parallel active power filter, the control of the active filter based on the inverter was then studied, namely the methods of identification of the reference harmonic currents: in this case we used the instantaneous power method pq, the hysteresis control for the inverter and a proportional regulator or fuzzy logic regulator for continuous bus regulation. Then, we will validate by simulations under the Simulink / Matlab environment. The results obtained by simulation show the efficiency and good performance of the parallel active filter. " " توفر الطاقة الكهربائية، التي يتم إنتاجها وتوزيعها بشكل أساسي على شكل جهد جيبي ثلاثي الطور، الطاقة الكهربائية اللازمة للأحمال المختلفة على الشبكة الكهربائية هذا الأخير يسجل زيادة في الاضطرابات بسبب الزيادة في الأحمال غير الخطية في العدد والنوع. لقد ثبت أن الحلول التقليدية غير كافية من خلال الترويج لبعض المكونات الجديدة السريعة لإلكترونيات الطاقة، ظهرت حلول حديثة وفعالة، ويتناول العمل المقدم في هذه الأطروحة حلا للتحكم في التلوث التوافقي وهو المرشح الموازي النشط في هذه الرسالة، نقدم دراسة ومحاكاة المعوض النشط المتوازي ذي المستويين المعلمتان اللتان تتطلبان ضبطا دقيقا لتعويض أفضل هما جهد مصدر تغذية العاكس مرشح نشط) والتيار أو الجهد التوافقي. بعد التذكير بالأصول وتأثيرات التلوث التوافقي على الشبكات الكهربائية، الحلول المختلفة لتنظيف الشبكة الكهربائية؛ قمنا بدراسة بنية مرشح القدرة النشط المتوازي، ثم تمت دراسة التحكم في المرشح النشط القائم على العاكس، والطرق المستعملة لتحديد التيارات التوافقية المرجعية في هذه الدراسة استخدمنا طريقة الاستطاعة اللحظية pq التحكم في التخلفية للعاكس والمنظم النسبي أو المنظم المنطق الضبابي لتنظيم الجهد المستمر بعد ذلك، سوف نتحقق من الصحة عن طريق عمليات المحاكاة في بيئة Simulink / Matlab تظهر النتائج التي تم الحصول عليها عن طريق المحاكاة كفاءة وأداء المرشح النشط المتوازي.
des thèses commande Electriqueمذكرات ماستر تخصص تحكم كهربائي
Keywords: "Harmonic current, total harmonic distortion, shunt active power filter, inverter, method (p-q). "; التيارات التوافقية ، معامل تشويه التيار ، المرشح الفعال المتوازن ، المرشح ، طريقة pq